Boston Public Library, ca. 1895 (Tufts Archival Research Center, 2005)
Street-level view south-southwest of the Boston Public Library, located on Dartmouth Street at Copley Square, between Boylston Street to the north-northwest and Blagdon Street to the south-southeast. The facade of the library faces east-northeast towards Dartmouth Street and Copley Square. Electricity lines, poles and street lights line Boylston Street. A trolley bus filled with passengers runs on its tracks down Boylston Street. A man stands on the sidewalk at the southeast corner of Boylston and Dartmouth Streets. Copyprint; designed by McKim, Mead and White, 1887-1895 7 1/4 x 9 3/8 Photographs